PEMANFAATAN GAME BLOOKET DALAM MATA PELAJARAN AKIDAH AKHLAK DI SMP DJAMA’ATUL ICHWAN SURAKARTA TAHUN AJARAN 2025/2026 - Diah Novita Fardani; Amy Mustauda (STKIP Subang, 2026)
The rapid development of digital technology has encouraged the adoption of more interactive assessment practices that align with students’ learning characteristics. However, assessment activities in Akidah Akhlak education are still predominantly conducted using conventional methods, which often fail to maximize student engagement and learning motivation. This study aims to investigate the implementation of Blooket as an assessment tool in Akidah Akhlak learning and to identify the supporting and inhibiting factors influencing its use at SMP Djama’atul Ichwan Surakarta. This study employed a descriptive qualitative approach involving an Akidah Akhlak teacher as the research subject, while Grade VIII students and the Vice Principal for Curriculum served as informants. Data were collected through observations, interviews, and documentation and were analyzed descriptively. The findings revealed that Blooket was used as a formative assessment tool following the delivery of the topic Practicing Noble Character Traits, including husnudzan (positive thinking), tawadhu’ (humility), tasamuh (tolerance), and ta’awun (mutual assistance). Its implementation involved three stages: planning, implementation, and evaluation. The use of Blooket enhanced students’ motivation, enthusiasm, engagement, and concentration during the assessment process. The question repetition feature helped strengthen students’ understanding, while the automatic scoring feature enabled teachers to conduct assessments more effectively and efficiently. Supporting factors included students’ familiarity with digital technology, support from the Islamic Digital Class (IDC) program, the availability of facilities and infrastructure, and teachers’ competence in managing digital assessments. Inhibiting factors included unstable internet connectivity, limited instructional time, potential distractions from digital devices, and Blooket’s limited capacity to comprehensively assess students’ affective competencies